SERPINE1 maintained expression by NR4A1 promotes invasion and migration of glioblastoma in hypoxic microenvironment - Tao, Zhennan; Sun, Yi; Yilamu, Yimuran; Xu, Bo; Yu, Chen; Zhang, Hao; Wu, Lingyun; Yu, Wanli; Dai, Yuxiang (Frontiers in Oncology, 2026)
IntroductionThe activation of epithelial mesenchymal transition (EMT) characteristics in GBM cells is the main factor leading to this invasion and migration. Serpin family E member 1 (SERPINE1) encodes plasminogen activator inhibitor-1 (PAI-1), which plays a key role in regulating the extracellular matrix and is closely related to tumor progression and metastasis, especially in gliomas. However, the exact molecular mechanism of its role in GBM is still unclear.MethodsIn this study, we evaluated the targeted therapeutic value of SERPINE1 through bioinformatics analysis. Study the effect of SERPINE1 inhibition on GBM cell proliferation and invasion using in vitro and in vivo models. Observe the EMT characteristics of hypoxia induced GBM cells and analyze the interaction between NR4A1 and SERPINE1 through molecular biology methods.ResultsOur research results indicate that GBM cells cultured in a low oxygen microenvironment have higher invasiveness, characterized by the activation of EMT markers. Inhibition of SERPINE1 in vitro can significantly reduce the proliferation and invasion ability of GBM cells. Further in vivo experiments have confirmed that targeting SERPINE1 can effectively inhibit the growth of GBM, reduce tumor size and proliferation in mouse models. In addition, we found that SERPINE1 can bind to NR4A1 and may have an interaction.ConclusionThis study provides new insights into the molecular mechanisms underlying the progression of GBM, emphasizing the role of SERPINE1 and its interaction with NR4A1 in promoting EMT and tumor invasion. Inhibiting the expression of SERPINE1 in GBM cells can prevent cell invasion, providing a potential strategy for the treatment of GBM.